Mental health indicators in APEC. (March 2019) - Kron, Michael; Grewal, Rupinder; Idso, John; Prough, Michael; Sundaram, Cassandra; Klein, Scott; Nida, John; Jumbam, Desmond; Garringer, Kaya
Background: The World Economic Forum (2011) concluded that the economic impact of mental illness is the single most important contributor among all non-communicable diseases to loss of productivity. The 21 economies represented by Asia Pacific Economic Cooperation (APEC) responded to that information with efforts to address mental health as an integral component of economic development. Aim: In order to help assess the progress of APEC region compared to other regions of the world, the World Health Organization (WHO) granted us access to a subset of the 2014 Mental Health Atlas database containing health indicators from all 21 APEC economies. Methods: APEC-specific data were extracted using the same format used by WHO in its Mental Health Atlas to compare/contrast data in APEC versus the six WHO regions of the world. Results: It was observed that mental health workforces in APEC include a higher number of psychiatrist providers compared with WHO regions. Suicide rates reported in three APEC economies are among the highest in the world. All APEC economies continue their individual and coordinated efforts to support their ' APEC Roadmap to Promote Mental Wellness in a Healthy Asia Pacific (2014–2020) '. Conclusion: Significant challenges for APEC members exist to coordinate regional efforts to improve mental health due to highly variable income levels, existing health infrastructures and social preferences. The findings in this report may serve as a helpful baseline for measuring success within the APEC region by 2020, the year in which progress in support of economic development will be reassessed.